Analisis Efektivitas Digital Marketing Dan Media Sosial Dalam Meningkatkan Loyalitas Konsumen Di Era Ekonomi Digital - Gulo, Vallery Tasa Leora Pontifek Sion (CV. SINAR HOWUHOWU, 2026)
This study aims to analyze how economic digitalization acts as a catalyst for Indonesia's Gross Domestic Product (GDP) growth by strengthening the Micro, Small, and Medium Enterprises (MSMEs) sector. Using descriptive qualitative methods and a literature review, this study finds that the adoption of digital technology by MSMEs improves operational efficiency, expands market reach, and enhances financial inclusion. The analysis shows that MSMEs' contribution to GDP increases along with the penetration of e-commerce and digital payment platforms, ultimately strengthening national economic resilience in the era of digital transformation.